ACCOUNTING STATEMENTS FOR PUBLICATION. - Miller, Herbert E. (The Accounting Review, 1942)
Abstract This article focuses on published accounting statements. Published statements should permit a variety of sound uses by the many groups (owners, creditors, management, employees, government, and the general public) who rightly are entitled to adequate, unambiguous disclosure. Furthermore, it seems reasonable to suggest that excellence in statement presentation is co-ordinate with the conception of a business enterprise. As is generally recognized, some accounts automatically reflect current dollar values. These accounts either are active enough, have a balance of recent origin, or represent a determined money dam so that the account balance has a significance, at a given date, above a simply nominal dollar amount. Other accounts, mainly fixed and intangible assets, have no such natural "up-to-date" characteristics. It seems reasonable to expect that a portion of the misunderstanding attributable to price-level variations might be removed if the statement presentations revealed the approximate dates of significant investments in fixed assets. Perhaps a considerable amount of confusion on this score arises from a deficiency of supplementary supporting schedules. If sufficient detail about certain account balances or classifications were available for the interested statement user, better results might be forthcoming.